Pengaruh Kepemimpinan dan Iklim Kerja Terhadap Semangat Kerja Guru - Damanik, Bahrudi Efendi (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2019)
This study aims to determine the effect of leadership on work morale, the influence of the work climate on work morale, and the influence of leadership and work climate on work morale in Pematangsiantar 4 Middle School. The method used in this study can be classified in the type of associative research that is a complete description of information about the relationship between variables one with other symptoms. The data analysis technique used in this study is multiple linear regression analysis, classic assumption test, t test, F test and determinant coefficient. The results of the analysis show that leadership partially has a positive and significant effect on morale, tcount> ttable (3.838> 1.697), the work climate partially has a positive and significant effect on morale, with tcount> ttable (1853> 1.697), leadership and the work climate simultaneously has a positive and significant effect on work morale, with the value of Fcount> Ftable (32,250> 3,350).